ANALYSIS AND RESEARCH OF METHODS AND MEANS OF DIAGNOSTIC INSULATION OF ELECTRICAL EQUIPMENT - SHTUTS, ANDRII; ZOZULYAK, IHOR; BALABAN, DENYS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This scientific article presents a comprehensive analysis of the methods and tools for diagnosing the insulation of electrical power equipment. The relevance of the study is due to the aging of the insulation during the operation of the equipment, which carries with it the risks of emergency situations, interruptions in the power supply and significant losses. Advantages and disadvantages were analyzed for each diagnostic method and tool, such as accuracy, reliability, informativeness, time and resource consumption, ease of use. Based on the analysis of the results of their practical application, an assessment of the effectiveness of diagnostic methods and tools is given. In today’s rapidly developing world, electrical power equipment plays a key role in ensuring a stable supply of electricity for various industries and domestic consumers. One of the critical aspects of uninterrupted operation of electrical power systems is the reliability of insulation of electrical equipment. Failure to properly monitor and diagnose insulation conditions can lead to significant technical problems, including system failures, equipment failures, and even accidents. The work also considers the question of the economic efficiency of the introduction of modern diagnostic tools. It was determined that timely diagnosis and elimination of defects allows to reduce the costs of repair and replacement of equipment, as well as to minimize the risk of emergency situations. The reviewed literature provides examples of economic calculations that confirm the feasibility of investing in the development of diagnostic systems. Thus, the article "Comprehensive analysis of methods and means of diagnostics of insulation of electric power equipment" represents a comprehensive study of modern approaches to diagnostics of the state of insulation. The conducted analysis allows us to draw a conclusion about the need for a comprehensive approach to diagnostics, which takes into account both traditional and innovative methods, as well as the introduction of modern technologies to increase the accuracy and reliability of the assessment of the state of insulation. The recommendations and directions of development proposed in the article may be useful for specialists in the field of electric power, dealing with issues of diagnostics and monitoring of the state of electrical equipment. Therefore, the study of methods and means of insulation diagnostics is extremely important to ensure stable and safe operation of electric power equipment.